Integrating resource efficiency in business strategies: a mixed-method approach for environmental life cycle assessment in the single-serve coffee value chain. (1st March 2016) - von Geibler, Justus; Cordaro, Francesco; Kennedy, Katharina; Lettenmeier, Michael; Roche, Bruno
Abstract: Businesses are under increasing pressure to improve the resource efficiency of their products and services. There is a need for practical tools that enable businesses to implement resource efficiency in their value chains. In this paper, a mixed-method approach for assessing the life-cycle-wide use of natural resources in products and services is applied in a case study on a coffee value chain of the company Mars Incorporated. Material inputs along the entire chain were assessed quantitatively using the Material Input Per unit of Service method, while a semi-quantitative Hot Spot Analysis was performed to identify environmental hot spots. This mixed-method approach has been implemented for the first time in practice to assess the value-chain-wide resource consumption and environmental impacts within a specific value chain of Mars Incorporated. The paper concludes that combining the methods provides better insights into the value chain than using just one of either of the methods alone. For the company, the approach has proven to be practicable because it identifies improvement options and their value-chain-wide resource efficiency potential. Highlights: A mixed-method approach for environmental life cycle assessment is developed. It combines Hot Spot Analysis and Material Input Per unit of Service analysis. The resource efficiency potential of identified improvement options can be modeled. The approach is practicable for the focal company in the coffee case study. Easy-to-understand results facilitate communication and implementation.